Synthesis of Silver Nanoparticles and Gold Nanoparticles Used as Biosensors for the Detection of Human Serum Albumin-Diagnosed Kidney Disease - Tiarpa Thongwattana; Ronnakorn Chaiyo; Khanittha Ponsanti; Benchamaporn Tangnorawich; Patcharee Pratumpong; Surachet Toommee; Ratchapol Jenjob; Su-Geun Yang; Yardnapar Parcharoen; Sitakan Natphopsuk; Chiravoot Pechyen (Pharmaceuticals)
Background/Objectives: This study aims to develop a screen-printed carbon electrode (SPCE) modified with silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) for the detection of human serum albumin (HSA). The objectives include utilizing green synthesis methods for nanoparticle production and evaluating the electrochemical performance of the modified electrodes. Methods: AgNPs and AuNPs were synthesized using Phulae pineapple peel extract (PPA) as a reducing agent. The nanoparticles were characterized using UV-visible spectrophotometry (UV-vis), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and transmission electron microscopy (TEM). The electrochemical performance of AgNP/SPCE and AuNP/SPCE was assessed by cyclic voltammetry (CV) studies, and the electrodes were functionalized with anti-HSA antibodies for HSA detection. Results: Characterization revealed spherical nanoparticles ranging from 10 to 30 nm. Both AgNP/SPCE and AuNP/SPCE demonstrated improved electrochemical performance compared to bare SPCEs. The modified sensors could detect serum albumin concentrations from 10 to 400 μg/mL, with high correlation values of 0.97 and 0.99 for AgNPs and AuNPs, respectively. Conclusions: This research demonstrates the potential of using agricultural waste for green synthesis of nanoparticles and highlights the application of AgNPs and AuNPs in developing sensitive biosensing platforms for the detection of human serum albumin.